EKSPLORASI KINERJA LINGKUNGAN DAN STUKTUR KEPEMILIKAN SEBAGAI FAKTOR PENENTU PENGUNGKAPAN KEBERLANJUTAN: EXPLORATION OF ENVIROMENTAL PERFOMANCE AND OWNERSHIP STUCTURE AS DETERMINANTS OF SUSTAINABILITY DISCLOSURE - Rahmi, Fadhilatur; Nelly Sari, Ria; Afifah , Ulfa (Universitas Riau, 2025)
This research is a quantitive study that aims to determine the effect of enviromental performance, foreign ownership and institutional ownership on the disclosure of sustainability report of companies in the mining sector listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The sample in this study was companies in the mining sector taken using purposive sampling techniques so thas 26 samples were obtained that met the criteria for 3 years. Data analysis was carried out using descriptive analysis, classical assumptions tests, linear regression analysis and hypothesis testing with SPSS 30.0. The results of the study indicate that enviromental perfomance and foreign ownership have a positive effect on sustainability report disclosure. However, institutional ownership has no effect on sustainability report disclosure. The implication of this study is to emphasize the importance of corporate transparency in sustainability reporting to increase investor confidence and comply with regulations, as well as encourage more accountable and sustainable business practice.